Sistema de información web y móvil para agilizar la gestión operativa de la Biblioteca en la i.e. San José - Pacasmayo - Gil Iman, Johaira Solange (2019)
Nowadays, it is very strenuous that an entity does not rely on technology for the development and good management of its information, because when using this great tool it has achieved the optimization of processes, as well as efficiency, effectiveness, availability and security for a correct and timely decision making. Currently the operational processes that are developed in the I. E San José library are not automated and are inefficient, that is why the study objective was to employ the technology through the design and implementation of a: "SISTEMA DE WEB AND MOBILE INFORMATION TO EXPAND THE OPERATIONAL MANAGEMENT OF THE LIBRARY AT SAN JOSE - PACASMAYO IE "thus achieving automation and improvement of its operational processes that were carried out manually. The development of the system allows remote access to information, obtaining queries, reports, records (bibliographic material, freckles, reservations, loans). For implementation, PHP code was used with the Laravel framework, with MySql as the database manager, and the RATIONAL UNIFIED PROCESS (RUP) for Web applications was also used for the development. With the implementation of the web system and mobile application it was possible to reduce the search times and delay times in the processes carried out in the library, as well as a positive result with a favorable increase in the level of satisfaction of the users. regarding each process of operational management